LES ÉTUDIANTS POLONOPHONES FACE AUX VOYELLES NASALES FRANÇAISES - Gajos, Mieczysław (Neofilolog, 2019)
In the process of the acquisition of the sound system of French as a foreign language, Polish students face numerous difficulties at the level of recognition, differentiation and correct production of French vowels. This is true for oral and nasal vowels. This article concentrates on nasal vowels, and its aim is to present a comparative description of nasal vowels in Polish and French, including recent changes in their production. Moreover, the paper presents the study reporting difficulty with correct perception and articulation of French nasal vowels faced by advanced Polish learners of French. While the paper does not describe corrective procedures, it indicates the necessity of undertaking further studies aiming at optimizing the process of the acquisition of the sound system in a foreign language.